2022
DOI: 10.1155/2022/9306741
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Adsorption Behavior of Gas Molecules on FeN3-Doped Graphene

Abstract: Herein, we have investigated the adsorption behavior of gas molecules, including C2H2, H2S, SO2, SO3, and O2, on FeN3-doped graphene (FeN3-gra). The change of geometric stability, electric structure, and magnetic properties is discussed comprehensively. The results have demonstrated that the stability of the substrate is enhanced by the hybridization between Fe and N atoms in FeN3-gra. Besides, the Fe dopant can enhance the adsorption ability of gases on graphene. The gas molecules all exhibit high binding str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The generalized gradient approximation (GGA) with the Perdew–Burke–Ernzerhof (PBE) functional is used to describe the exchange and correlation potential [ 44 ]. The van der Waals (vdW) interaction between gas and surface of MnX-GN catalysts plays a key role in the adsorption; thus, gas adsorption on metal-doped graphene has been successfully studied with the vdW correction [ 46 , 47 ]. Therefore, the interaction of vdW is considered with DFT-3 in our work [ 48 ].…”
Section: Computational Details and Methodsmentioning
confidence: 99%
“…The generalized gradient approximation (GGA) with the Perdew–Burke–Ernzerhof (PBE) functional is used to describe the exchange and correlation potential [ 44 ]. The van der Waals (vdW) interaction between gas and surface of MnX-GN catalysts plays a key role in the adsorption; thus, gas adsorption on metal-doped graphene has been successfully studied with the vdW correction [ 46 , 47 ]. Therefore, the interaction of vdW is considered with DFT-3 in our work [ 48 ].…”
Section: Computational Details and Methodsmentioning
confidence: 99%
“…Among them, FeN 3 -doped carbon materials have shown excellent performance in previous studies, which will be beneficial to improve the current issues (such as heavy metal pollution and GHG emission) in agricultural fields. For example, Gao et al proved that FeN 3 -embedded carbon possesses a good mercury adsorption ability via the first-principles calculation (Gao et al 2019); Xie et al found that FeN 3 -doped graphene could adsorb the gas molecules (C 2 H 2 , H 2 S, SO 2 , SO 3 , and O 2 ) (Xie et al 2022). Thus, it is an efficient method to use the FeN 3 -doped biochar as the sorbent in paddy fields which are the main emission source for GHGs.…”
Section: Graphical Abstract 1 Introductionmentioning
confidence: 99%